Phenolic Composition of the Brazilian Seedless Table Grape Varieties BRS Clara and BRS Morena - Lago-Vanzela, Ellen Silva [UNESP]; Da-Silva, Roberto [UNESP]; Gomes, Eleni [UNESP]; Garcia-Romero, Esteban; Hermosin-Gutierrez, Isidro (Amer Chemical Soc, 2011)
The detailed phenolic composition (anthocyanins, flavonols, hydroxycinnamic acid derivatives, stilbenes, and flavan-3-ols) in the skin and flesh of the new BRS Clara and BRS Morena seedless table grapes has been studied using HPLC-DAD-ESI-MS/MS. The two grapes, especially BRS Morena, contained high amounts of phenolic compounds, mainly located in their skins and qualitatively not different from those found in Vitis vinifera grapes. In addition, BRS Morena (a teinturier variety) showed qualitatively different phenolic compositions in its skin and flesh, mainly affecting the anthocyanin and flavonol profiles. Consistent with high phenolic contents, high antioxidant capacity values were registered for both grape varieties, especially for BRS Morena. Proanthocyanidins and hydroxycinnamoyl-tartaric acids were the major phenolic compounds found in BRS Clara and were also important in BRS Morena, although anthocyanins were the main phenolic compounds in the latter case. These results suggest that the entire grapes, including the skin, may potentially possess properties that are beneficial to human health. In this context, the BRS Morena grape can be considered as a high resveratrol producer.
Keywords: anthocyanins; flavonols; proanthocyanidins; hydroxycinnamic acid; stilbenes; seedless table grapes; Antioxidant capacity; Phenolic compounds